PERLINDUNGAN KONSUMEN TERHADAP PRODUK MAKANAN DAN MINUMAN KADALUWARSA DI SUPERINDO SIDOARJO(KAJIAN YURIDIS UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN) - Selix Nur Aziz; Tuti Herningtyas (INTELIGENSIA MEDIA, 2024)
The purpose of this study is to determine and analyze the form of legal protection for consumers against expired food and beverage products at Superindo Sidoarjo supermarkets and to know and analyze consumer dispute resolution for unlawful acts committed by producers (business actors) against expired food and beverage products at Superindo Sidoarjo supermarkets. This research is included in juridical research. The results showed that the form of legal protection for consumers against expired food and beverage products at Superindo Sidoarjo supermarket consisted of preventive protection and repressive protection. Preventive legal protection focuses on preventive efforts, including providing a legal umbrella for consumers by regulating business actors and guaranteeing consumer rights and their protection through laws and regulations. Meanwhile, repressive laws are carried out in the form of enforcement efforts such as administrative sanctions, confiscation, criminal sanctions. Repressive legal protection can also be in the form of producer responsibility in terms of providing compensation for losses suffered by consumers as a result of the circulation and trade of expired food products. The results also show that the settlement of consumer disputes over unlawful acts committed by producers (business actors) against expired food and beverage products at Superindo Sidoarjo supermarkets is through consumer institutions regulated in Law Number 8 of 1999 concerning Consumer Protection. The parties involved in consumer disputes are consumers and business actors.